2013
DOI: 10.1021/nn3057356
|View full text |Cite
|
Sign up to set email alerts
|

Stoichiometric Control of Lead Chalcogenide Nanocrystal Solids to Enhance Their Electronic and Optoelectronic Device Performance

Abstract: We investigate the effects of stoichiometric imbalance on the electronic properties of lead chalcogenide nanocrystal films by introducing excess lead (Pb) or selenium (Se) through thermal evaporation. Hall-effect and capacitance-voltage measurements show that the carrier type, concentration, and Fermi level in nanocrystal solids may be precisely controlled through their stoichiometry. By manipulating only the stoichiometry of the nanocrystal solids, we engineer the characteristics of electronic and optoelectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
308
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(331 citation statements)
references
References 49 publications
20
308
1
2
Order By: Relevance
“…Another postsynthesis approach of electronic modification is stoichiometry control via deposition of excess lead or chalcogen. 42,43 Although neutral atomic vacancies are unlikely to form during solution synthesis (as discussed before), this postsynthesis control can produce QDs with excess Pb or S (i.e., QD with neutral S or Pb vacancies). According to previous calculations 8,16 and our own DFT results (not shown here), neutral Pb vacancies produce IGS near the valence band, while neutral S or L (ligand) vacancies produce IGS near the conduction band.…”
Section: Spectroscopic Evidence and Further Theoretical Support On Thmentioning
confidence: 99%
See 1 more Smart Citation
“…Another postsynthesis approach of electronic modification is stoichiometry control via deposition of excess lead or chalcogen. 42,43 Although neutral atomic vacancies are unlikely to form during solution synthesis (as discussed before), this postsynthesis control can produce QDs with excess Pb or S (i.e., QD with neutral S or Pb vacancies). According to previous calculations 8,16 and our own DFT results (not shown here), neutral Pb vacancies produce IGS near the valence band, while neutral S or L (ligand) vacancies produce IGS near the conduction band.…”
Section: Spectroscopic Evidence and Further Theoretical Support On Thmentioning
confidence: 99%
“…exhibit unintentional p-type doping even in inert atmosphere, with carrier densities of 10 16 À10 17 cm À3 for QDs of 5À6 nm diameter. 42 …”
Section: Spectroscopic Evidence and Further Theoretical Support On Thmentioning
confidence: 99%
“…This may happen via engineering of the composition, by doping or the formation of heterostructures. 19,[38][39][40][41][42] Colloidal oligomeric hybrid nanoparticles (HNPs) offer the possibility to tailor material combinations for advanced applications in the fields of photocatalysis and (opto-)electronics. 43,44 A number of studies have demonstrated the excellent photo-catalytic properties of metal-semiconductor HNPs in liquid solution, which are based on an efficient separation of photogenerated charge carriers.…”
mentioning
confidence: 99%
“…As the wavefunctions of charge carriers are spatially confined in a smaller volume than in the parental bulk material [49], it follows that the probability of finding charge carriers at the particle surface is greatly increased. The consequence of both effects is that, in QDs, a significant proportion of generated charge carriers will get trapped at surface sites that are energetically removed from the semiconductor's charge transport level [72]. This effect is exacerbated for MEG devices due to the requirement for strong confinement [73,74].…”
Section: Impacts Of the Qd Surface On Meg In A Device Environmentmentioning
confidence: 99%